1977
DOI: 10.1073/pnas.74.8.3537
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-controlled depletion of complement activity by spin-label-specific IgM

Abstract: Complement depletion mediated by high molecular weight (IgM) rabbit antibodies specifically bound to spin-label lipid haptens dispersed in model membranes is controlled by various physical attributes of those membranes other than the total number of exposed determinants that they provide. Carrier lipids used at 320 were (i) a "fluid" phosphatidylcholine (PC), (if) a "solid" PC, and (iil) a cholesterol/PC mixture.The concentration of hapten in the plane of the membranes (two-dimensional concentration) was varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The spectra of spin-label lipid haptens in membranes were rather anisotropic, and the low field peak was the narrowest of the three sharp lines. This characteristic coincided with the results obtained by Smith's group (Hsia et al, 1970;Schreier-Muccillo et al, 1973) using the stearamide spin-label and by McConnell's group (Bruilet et al, 1977;Brfulet and McConnell, 1977;Humphries and McConnell, 1977;Humphries, 1980) using the same spinlabel as us. According to Griffith and Jost (1976), axial rotation about the x-axis should result in the spectrum with the narrowest low field peak, while rotation about the other axes lead to the central peak being the narrowest.…”
Section: Discussionsupporting
confidence: 90%
“…The spectra of spin-label lipid haptens in membranes were rather anisotropic, and the low field peak was the narrowest of the three sharp lines. This characteristic coincided with the results obtained by Smith's group (Hsia et al, 1970;Schreier-Muccillo et al, 1973) using the stearamide spin-label and by McConnell's group (Bruilet et al, 1977;Brfulet and McConnell, 1977;Humphries and McConnell, 1977;Humphries, 1980) using the same spinlabel as us. According to Griffith and Jost (1976), axial rotation about the x-axis should result in the spectrum with the narrowest low field peak, while rotation about the other axes lead to the central peak being the narrowest.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is possible that the accessibility of anti-KMP-11 Abs may be due to the rigidity of the membrane, as shown by other workers with model membranes (26). An alternative possibility is that because of its ability to fold and unfold KMP-11 may interact with the membrane lipid (18).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies on the interaction of IgG antibody specific for 2,4-dinitrophenyl (Dnp) or paramagnetic nitroxide (spinlabel) ligands which were attached to a phosopholipid in the liposomal membrane indicated that a spacer between the phospholipid head group and the antigenic determinant facilitated the binding of specific antibody (Six et al, 1973(Six et al, , 1974; Brület & McConnell, 1976Humphries & McConnell, 1977). We, therefore, synthesized a probe which incorporated lysine as a spacer in order to separate the phospholipid head group and the haptenic group by 10-12 Á.…”
Section: Resultsmentioning
confidence: 99%